Forecast Parameters Disintegration and Coordination of The Socio-Economic Development and Fuel and Energy Balance of a Region - Dobrodey, Vladimir Vavilovich (Economy of Regions, 2015)
At the present time, the document contents of strategic planning for subjects of the Russian Federation, their order of development and endorsement at the interregional and federal levels, requirements for content and coordination with other long-term and medium-term territorial programs are legislative authorized. In the article, the theoretical and methodical problems of specification and interrelation of forecast scenario versions of region socio-economic development with expected parameters of regional energy consumption on the basis of fuel and energy balance in the conditions of incomplete retrospective information are considered. Such situation is typical in the market conditions, and some restrictions on access to the statistical data can be removed. It reduces the application of the strict formal valuation methods and objectivity not only expected, but also current indicators. Methodical and practical relevance of coordination of the specified documents is caused by the relative isolation of their development, various specification level of expected scenarios, lack of necessary information. The authors use the estimation procedure of indicators of energy saving and energy efficiency based on structural comparison of real, current, and expected fuel and energy balances coordinated with the forecast of region socio-economic development and are interested in its development for the comparative analysis of regional energy consumption in the retrospective and expected periods. The calculations are carried out by the authors since 2007 within the state order of the Ministry of Energy and Housing and Utilities Infrastructure of the Sverdlovsk region. In the article, the methodical features of the author's approaches to the option development of fuel and energy balance considering official scenarios of the forecast of region socio-economic development, fault and incompleteness of statistical data, standard requirements for the forecasts quality are reflected.